HUBUNGAN EFEKTIVITAS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DENGAN KEMANDIRIAN BELAJAR MAHASISWA PENDIDIKAN AGAMA ISLAM UIN-SU MEDAN - Muhammad Rahmadani; Andreo Diwa Arsenta; Muhammad Aprijal; Alfikri; Arlina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine whether there is a significant relationship between the effectiveness of using Artificial Intelligence (AI) and the self-regulated learning of Islamic Education (PAI) students, academic year 2023 at UIN Sumatera Utara. This research employs a quantitative correlational approach. Data collection was conducted through a questionnaire instrument distributed to a sample of 77 respondents. The data analysis technique used was the Pearson Product-Moment correlation test, applied after ensuring the data met the prerequisites of normality and linearity tests. The descriptive analysis results indicate that both the effectiveness of AI usage and the students' self-regulated learning are in the moderate category. Based on the hypothesis testing, a pearson correlation of 0.021 with a significance value of 0.854 was obtained. Because the significance value is greater than 0.05 (0.854 > 0.05), H0 is accepted and H1 is rejected. This confirms that there is no significant relationship between the effectiveness of using Artificial Intelligence (AI) and students' self-regulated learning. The conclusion of this study indicates that Artificial Intelligence (AI) technology purely serves as an external assistive tool and is incapable of automatically shaping self-regulated learning. Self-regulated learning is proven to be an aspect driven by internal factors, specifically the awareness and motivation from within the learners themselves.